Makna Mengasihi Bukan dengan Perkataan Atau Dengan Lidah Berdasarkan 1 Yohanes 3:18 - Agustia, Viki (Views : Jurnal Teologi dan Biblika, 2025)
This study examines the meaning of the command in 1 John 3:18, which emphasizes that love must be demonstrated through deeds and truth, not merely words or tongue. As the core teaching of the Apostle John—the “apostle of love”—this verse is relevant in the historical context of the early Christian community facing false teachings, where genuine love needed to be distinguished from empty rhetoric. The study's purpose is to explore the theological and practical implications of this verse, focusing on the manifestation of authentic love through concrete actions, emulating Christ's sacrifice. Believers are called to demonstrate love through concrete concern for the needy, including counsel, rebuke, and warnings that encourage growth in righteousness, not cover up errors. An exegetical analysis of the verse and context of 1 John finds that God's love is active, sincere, and aligned with biblical teaching. Conclusion: Love is a concrete commitment that reflects divine truth, challenging believers to live it out in all aspects of life.